The Relationship Between Levels Of Spiritual Welfare and Anxiety in Elderly - Wisnusakti, Khrisna (JURNAL PENDIDIKAN KEPERAWATAN INDONESIA, 2018)
ABSTRACTAnxiety is a normal emotional reaction to stress and perceptions of danger, feelings are not calm and unclear because of helplessness, isolation and spiritual insecurity are the beliefs of our relationship with God Almighty and Creator, it permeates the lives of people who we are and our purpose. The purpose of this study was to determine the relationship between the spiritual level of anxiety in elderly. Quantitative research method with cross sectional approach. The sample in this study were 98 respondents by using total sampling. Data processing with Chi-Square technique. The instrument used in data retrieval was a questionnaire. The results showed that the elderly had a high spiritual level of 76 people (77.6%), the elderly did not worry as many as 85 people (86.7%). Statistical test results showed there was a relationship between spiritual levels against anxiety (p value = 0.01 α = 0.05) in the elderly. Suggestions for nurses to maintain the spiritual activities that are in place to prevent anxiety in the Elderly. ABSTRAKKecemasan merupakan reaksi emosional yang normal terhadap stress persepsi adanya bahaya, perasaan yang tidak tenang dan tidak jelas karena ketidakberdayaan, isolasi dan ketidakamanan. Spiritual adalah keyakinan hubungan kita dengan Tuhan Yang Maha Kuasa dan Maha Pencipta, hal itu meresap kedalam kehidupan manusia akan sadarnya siapa diri kita dan tujuan kita. Tujuan penelitian untuk mengetahui hubungan tingkat spiritual terhadap kecemasan pada lansia. Metode penelitian kuantitatif dengan pendekatan cross sectional. Sampel dalam penelitian ini sebanyak 98 responden dengan cara menggunakan total sampling. Pengolahan data dengan teknik Chi-Square. Instrumen yang digunakan dalam pengambilan data adalah kuesioner. Hasil penelitian menunjukkan lansia memiliki tingkat spiritual yang tinggi sebanyak 76 orang (77,6%), lansia tidak cemas sebanyak 85 orang (86,7%). Analisa dari hasil uji statistik tersebut adalah terdapatnya hubungan antara tingkat spiritual terhadap kecemasan (p value = 0,01 α = 0,05) jadi semakin tinggi tingkat spiritual lansia maka semakin rendah angka kejadian kecemasan pada lansia. Saran bagi perawat mempertahankan kegiatan spiritual yang ada dipanti untuk mencegah terjadinya kecemasan pada Lansia.